2022
DOI: 10.5653/cerm.2021.04875
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of complication rates after transvaginal ultrasound-guided oocyte pick-up procedures with respect to ovarian response

Abstract: Objective: The aim of this study was to compare the complication rates of oocyte pick-up (OPU) procedures via transvaginal ultrasonography in patients with different levels of ovarian reserve. Methods: In total, 789 patients who underwent OPU procedures for in vitro fertilization (IVF) were included in the study.Results: Individuals with normal ovarian reserve had a 2.947-fold higher risk of complications in OPU procedures than individuals with low ovarian reserve, and individuals with high ovarian reserve had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Therefore, rather than continuing with CC alone, especially in PCOS patients who are CC-resistant, CC might be coupled with metformin. 41,42 However this is also accompanied by a rise in multiple pregnancies (5-8%) and ovarian hyperstimulation syndrome (1%). 42 Antiandrogens Spironolactone, flutamide, and finasteride are antiandrogens that slow the development of new terminal hairs, which can be used to treat symptomatic complications of hyperandrogenism due to PCOS.…”
Section: Metforminmentioning
confidence: 99%
“…Therefore, rather than continuing with CC alone, especially in PCOS patients who are CC-resistant, CC might be coupled with metformin. 41,42 However this is also accompanied by a rise in multiple pregnancies (5-8%) and ovarian hyperstimulation syndrome (1%). 42 Antiandrogens Spironolactone, flutamide, and finasteride are antiandrogens that slow the development of new terminal hairs, which can be used to treat symptomatic complications of hyperandrogenism due to PCOS.…”
Section: Metforminmentioning
confidence: 99%
“…3 This complication is seen in reproductive age and affects about 5% of women at this age. 4 Today, studies have shown that various genetic and environmental factors cause PCOS, all of which are involved in the pathophysiology of this occurrence. 3 The definition of PCOS includes hyperandrogenism without a specific cause, such as an androgen-producing tumor, congenital adrenal hyperplasia with late-onset, lack of ovulation, the appearance of polycystic ovaries on ultrasound in the form of more than eight follicles with a size of 2 to 8 mm, and the increase of ovarian stroma.…”
Section: Introductionmentioning
confidence: 99%
“…AMH is a member of the large TGF_B beta factor family, secreted by the granulosa cells of small follicles to regulate the initial stages of follicle growth. AMH is used to predict and determine ovarian reserve and the quality of remaining oocytes (5,6).…”
Section: Introductionmentioning
confidence: 99%